2018
DOI: 10.1097/olq.0000000000000875
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Reverse Algorithm Syphilis Screening in a High Prevalence Population

Abstract: Using the reverse algorithm would have been slightly more expensive for the Los Angeles County Department of Public Health, but would have identified more syphilis cases and would have resulted in lower laboratory costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…On the heels of groundbreaking advances in the cultivation and genomic analysis of T. pallidum, [16][17][18] the development of new, highly sensitive, and specific treponemal immunoassays promised accuracy, efficiency, and cost savings for highvolume laboratories. 19 The Abbott ARCHITECT syphilis TP chemiluminescent immunoassay is highly precise and accurate for laboratory diagnosis of past or current syphilis in pregnancy when compared with reference standard TPPA, and relative S/CO ratio may be useful in identifying cases of clinically infectious syphilis to aid in triage and management of exposed neonates. Importantly, a thorough clinical history and staging evaluation by the obstetrician remains essential for early identification and treatment of the pregnant patient with syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…On the heels of groundbreaking advances in the cultivation and genomic analysis of T. pallidum, [16][17][18] the development of new, highly sensitive, and specific treponemal immunoassays promised accuracy, efficiency, and cost savings for highvolume laboratories. 19 The Abbott ARCHITECT syphilis TP chemiluminescent immunoassay is highly precise and accurate for laboratory diagnosis of past or current syphilis in pregnancy when compared with reference standard TPPA, and relative S/CO ratio may be useful in identifying cases of clinically infectious syphilis to aid in triage and management of exposed neonates. Importantly, a thorough clinical history and staging evaluation by the obstetrician remains essential for early identification and treatment of the pregnant patient with syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…These data are not consistent with a study that reported the reverse sequence algorithm as being cost-effective when applied to screening lower-prevalence prenatal and nonprenatal populations with a syphilis prevalence of 0.076% and 1.94%, respectively ( 90 ). In an economic impact model on a local sexually transmitted diseases (STD) program in Los Angeles County, California, the reverse algorithm was less expensive and identified more patients for treatment if the cost of the treponemal test was $1.67 less than the nontreponemal (lipoidal antigen) test cost of $5.80 ( 91 ). Testing, treatment, and follow-up costs were included in the analysis.…”
Section: Recommendations For Syphilis Testing In the United Statesmentioning
confidence: 99%
“…A study in Canada concluded that the reverse algorithm was more cost-effective than the traditional algorithm (Chuck et al, 2008). In contrast, a study in the U.S. reported that the reverse algorithm would be more expensive in terms of public health (Buono et al, 2018). Despite the slight increase in false-positive cases, the reverse algorithm can detect substantial cases missed by the traditional algorithm.…”
Section: Algorithmsmentioning
confidence: 99%